Phytochemical richness, antioxidant activity, and molecular diversity in Papaver species from Iran’s western and central regions - Nazari, Naser; Sharifnia, Fariba; Salimpour, Fahimeh; Mehrnia, Mohammad; Gran, Afsaneh; Zarafshar, Mehrdad (Frontiers in Plant Science, 2025)
This study examined the phytochemical diversity, antioxidant capacity, and genetic relationships among Papaver species collected from western and central Iran. Significant interspecific and regional variation was observed in total phenolic and flavonoid contents, with P. hybridum from Khuzestan showing the highest phenolic (50.26 mg GAE/g DW) and antioxidant activity (DPPH: 70.40%, FRAP: 6.91 µmol Fe²+/g DW). P. macrostomum and P. dubium also exhibited notable flavonoid and anthocyanin levels, respectively. Codeine content peaked in P. hybridum, while papaverine was highest in P. dubium. Antioxidant traits correlated strongly with phenolic content and environmental variables such as humidity and elevation. PCA revealed clustering of antioxidant traits, while alkaloids and anthocyanins formed distinct patterns. Phylogenetic analysis indicated complex evolutionary relationships and possible introgression among species. These findings highlight substantial phytochemical and genetic variation shaped by local environments. As this study focuses on Iranian populations, broader geographic sampling is needed to generalize the patterns observed.